Identifying the influence of micro profile of rural roads on the durability of bus body when carrying passengers - Ruban, Dmytro; Krainyk, Lybomyr; Ruban, Hanna; Khimka, Stepan; Sukach, Oleg; Khotunov, Vladyslav; Shevchuk, Viktor; Dufanets, Ihor; Artyukh, Оlexandr (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the durability of a bus body when passengers are transported on rural roads. According to the European classification, the total length of roads in Ukraine that correspond to the first category does not exceed 5 %. That is, all other 95 % of roads have a quality level that does not meet the regulatory operating conditions. In particular, in rural areas, buses are operated both on worn asphalt-concrete surfaces and on dirt and gravel roads. Such operating conditions additionally lead to intensive wear of buses and significantly worsen the durability of their bodies. The task to determine the influence of worn and dirt roads on the durability of the bus body during passenger transportation in rural areas could be solved by the durability assessment procedure proposed in this paper. The current work presents patterns that make it possible to predict the degradation of the bus body material that affect the durability of the body. The factors of influence during the operation of buses on rural routes have been substantiated and presented. The simulation results show that when operating buses on rural roads, cracks in the body frame of the body occur at runs that are 3.8–13.1 times less than under regulatory operating conditions. The proposed procedure for assessing the durability of a bus body when transporting passengers on rural roads makes it possible to predict the deterioration of the physical and mechanical properties of the elements of the bus body frame and take measures at the design stage to increase their reliability and durability